Efficacy of Different Hair and Skin Decontamination Strategies with Identification of Associated Hazards to First Responders. (3rd May 2020) - Larner, Joanne; Durrant, Adam; Hughes, Philip; Mahalingam, Devanya; Rivers, Samantha; Matar, Hazem; Thomas, Elliot; Barrett, Mark; Pinhal, Andreia; Amer, Nevine; Hall, Charlotte; Jackson, Toni; et al.
Abstract: Background: Established procedures for mass casualty decontamination involve the deployment of equipment for showering with water (such as the ladder pipe system [LPS] and technical decontamination [TD]). This necessarily introduces a short, but critical delay. The incorporation of dry decontamination to the incident response process offers the potential to establish a more rapid and timely intervention. Objectives: To investigate the effectiveness of various dry (DD) and wet decontamination strategies for removing a chemical warfare simulant (methyl salicylate; MS) from the hair and skin of human volunteers. Methods: The simulant was applied to volunteers via whole body exposure to an aerosol. Three decontamination protocols (dry, LPS and technical decontamination) were applied, singly and in various combinations. The efficacy of the protocols was evaluated by fluorescent photography and analysis of residual MS from skin/hair swabs, decontamination materials and air samples. Results: Dry decontamination was effective, with the greatest reduction in skin and hair contamination arising from the "Triple Protocol" (DD+LPS+TD). Secondary hazards associated with contaminated individuals and equipment decreased as the number of decontamination procedures increased. In particular, dry decontamination reduced the potential contact and inhalation hazard arising from used washcloths, towels and vapor within the TD units. Discussion: The introduction of dry decontamination prior to wet forms of decontamination offers a simple strategy to initiate treatment at a much earlier opportunity, with a corresponding improvement in clinical outcomes and substantial reduction of secondary hazards associated with operational processes.